Alkali complexes of non-steroidal anti-inflammatory drugs inhibit lung and oral cancers in vitro. (10th December 2020) - Shah, Syed Raza; Shah, Zarbad; Khan, Ajmal; Ahmed, Ayaz; Khwaja, Shariqa; Csuk, Rene; Anwar, Muhammad U.; Al-Harrasi, Ahmed
Abstract : Alkali metal complexes (Li, K, and Cs) displayed excellent activities against oral and lung cancer cells with the least toxicity toward normal cells. Abstract : Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used to treat pain, fever, and inflammation. In this paper, we report four new alkali metal complexes (1–4 ) containing 1, 10-phenanthroline (phen ), and two NASID drugs, that is, ibuprofen (ibu ) and flurbiprofen (fibu ). Complexes 1–4 were characterized by a variety of analytical techniques including infrared and UV-vis spectroscopy, 1 H NMR, and single-crystal and powder X-ray diffraction analysis. In complexes 1–4, phen binds via an N, N ′-chelate pocket, while the ibu and fibu ligands coordinate in a bidentate fashion in all four complexes. The complexes were evaluated for their anticancer activity against lung and oral cancer cell lines. The complexes displayed excellent activities against oral and lung cancer cells with the least toxicity toward normal cells when compared to the standard drug 5-fluorouracil .